Massively‐parallel sequencing assists the diagnosis and guided treatment of cancers of unknown primary. Issue 4 (12th November 2013) - Tothill, Richard W; Li, Jason; Mileshkin, Linda; Doig, Ken; Siganakis, Terence; Cowin, Prue; Fellowes, Andrew; Semple, Timothy; Fox, Stephen; Byron, Keith; Kowalczyk, Adam; Thomas, David; et al.
Abstract: The clinical management of patients with cancer of unknown primary (CUP) is hampered by the absence of a definitive site of origin. We explored the utility of massively‐parallel (next‐generation) sequencing for the diagnosis of a primary site of origin and for the identification of novel treatment options. DNA enrichment by hybridization capture of 701 genes of clinical and/or biological importance, followed by massively‐parallel sequencing, was performed on 16 CUP patients who had defied attempts to identify a likely site of origin. We obtained high quality data from both fresh‐frozen and formalin‐fixed, paraffin‐embedded samples, demonstrating accessibility to routine diagnostic material. DNA copy‐number obtained by massively‐parallel sequencing was comparable to that obtained using oligonucleotide microarrays or quantitatively hybridized fluorescently tagged oligonucleotides. Sequencing to an average depth of 458‐fold enabled detection of somatically acquired single nucleotide mutations, insertions, deletions and copy‐number changes, and measurement of allelic frequency. Common cancer‐causing mutations were found in all cancers. Mutation profiling revealed therapeutic gene targets and pathways in 12/16 cases, providing novel treatment options. The presence of driver mutations that are enriched in certain known tumour types, together with mutational signatures indicative of exposure to sunlight or smoking, added to clinical, pathological, and molecular indicators of likely tissue of origin. Massively‐parallel DNA sequencing can therefore provide comprehensive mutation, DNA copy‐number, and mutational signature data that are of significant clinical value for a majority of CUP patients, providing both cumulative evidence for the diagnosis of primary site and options for future treatment. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.